Play, space, and the magic circle: Reinventing the game - Robin Hartanto Honggare; Fauzia Evanindya (Department of Architecture Faculty of Engineering Universitas Indonesia, 2021)
In 2020, Dolanan, a collaborative practice exploring the architectural possibilities of play embedded in Indonesian traditional games, launched its pilot project titled Makan Kerupuk, which experimented on the spatial aspect of the crackers eating game often played during the Independence Day of Indonesia. Driven both by Johan Huizinga’s conceptualisation of the magic circle and the global pandemic, which prevented people from gathering in public space, this project probed into the limit of conventional play-arena by distributing the sites of play into multiple domesticities. Utilising both real and virtual means, Dolanan enacted a version of the game in which participants could engage with the physical experience of playing by employing a dispersal strategy, without dismissing the sense of publicness that marked the national holiday. Images produced by the participants are further analysed in this paper to reflect on the state of the magic circle as conveyed and experienced through this project.